2016
DOI: 10.1002/eji.201646599
|View full text |Cite
|
Sign up to set email alerts
|

Survival of mature T cells in the periphery is intrinsically dependent on GIMAP1 in mice

Abstract: An effective immune system depends upon the survival of mature T cells in the periphery. Members of the GIMAP family of GTPases have been proposed to regulate this homeostasis, supported by the paucity of peripheral T cells in rodents deficient for either GIMAP1 or GIMAP5. It is unclear whether this lack of T cells is a consequence of an ontological defect, causing the thymus to generate and export T cells incapable of surviving in the periphery, or whether (alternatively or additionally) mature T cells intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…In this study, we used the TCGA and GEO databases to report down-regulation of hGIMAPs in NLCSC and analyzed that low expression of all seven GIMAP genes was associated with poor prognosis, which is consistent with shiao et al [13]. GIMAPs are generally considered to be T cell receptor stress molecules and function primarily to exert anti-apoptotic effects in the immune system [14][15][16]. The current study found that GIMAPs are present in exosomes and significantly down-regulated in the PBMC cells of lung cancer patients [17][18][19].…”
Section: Discussionsupporting
confidence: 73%
“…In this study, we used the TCGA and GEO databases to report down-regulation of hGIMAPs in NLCSC and analyzed that low expression of all seven GIMAP genes was associated with poor prognosis, which is consistent with shiao et al [13]. GIMAPs are generally considered to be T cell receptor stress molecules and function primarily to exert anti-apoptotic effects in the immune system [14][15][16]. The current study found that GIMAPs are present in exosomes and significantly down-regulated in the PBMC cells of lung cancer patients [17][18][19].…”
Section: Discussionsupporting
confidence: 73%
“…Studies of rats carrying a natural mutation of the Gimap5 gene [ 11 , 12 , 42 , 43 ] and mice carrying targeted or chemically-induced mutations of the orthologous gene [ 13 , 14 ] have shown that it is required for the establishment/maintenance of normal T and (to a lesser extent) B cell lymphocyte populations. Similarly, mice carrying a targeted mutation of the Gimap1 gene in the lymphoid lineages lack T cells [ 17 , 44 ], although in this case there seems to be an equally strong effect on B cells [ 36 ]. A third membrane-anchored member of the family (GIMAP3) has also been demonstrated to be involved in T cell maintenance, although only when also linked to inactivation of GIMAP5 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However in contrast to GIMAPs 3, 4 and 5 reported on by Nitta and co-workers [ 7 ], Ho and colleagues were unable to demonstrate an interaction of GIMAP6 with any obvious apoptosis-associated protein, raising the possibility that GIMAP6 may be inducing apoptosis by a distinct route. This possibility has been strengthened by genetic and cellular studies of the lymphopenias and cell death associated with GIMAP5 and GIMAP1 deficiencies [ 14 , 36 , 44 ] which cast doubt on the involvement of the BCL2-related apoptotic machinery in the lymphopenias.…”
Section: Discussionmentioning
confidence: 99%
“…And the execution of programmed cell death directly correlates with the phosphorylation status of GIMAP4 [ 22 ]. Datta P et al also reported that GIMAP1 ablation is accompanied by activation of the extrinsic apoptotic pathway [ 23 ]. Given that pathway and Reactome analyses of GIMAPs, it is likely that GIMAPs are involved in molecular pathogenesis of cancer via regulation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%